(untitled) (Clinics, 2013)
OBJECTIVES: Biological markers that predict the development of invasive breast cancer are needed to improve personalized therapy for patients diagnosed with ductal carcinoma in situ. We investigated the role of basal cytokeratin 5/6 in the risk of invasion in breast ductal carcinoma in situ. METHODS: We constructed tissue microarrays using 236 ductal carcinoma in situ samples: 90 pure samples (group 1) and 146 samples associated with invasive carcinoma (group 2). Both groups had similar nuclear grades and were obtained from patients of similar ages. The groups were compared in terms of estrogen (ER) and progesterone receptor (PR) status, human epidermal growth factor receptor 2 (HER2) expression, cytokeratin 5/6 immunostaining, human epidermal growth factor receptor 1 (EGFR) membrane staining and molecular subtype, as indicated by their immunohistochemistry profiles. RESULTS: ER/PR-negative status was predictive of invasion, whereas HER2 superexpression and cytokeratin 5/6-positive status were negatively associated with invasion. Among the high-grade ductal carcinoma in situ cases, a triple-positive profile (positive for estrogen receptor, progesterone receptor, and HER2) and cytokeratin 5/6 expression by neoplastic cells were negatively associated with invasion. In the low-grade ductal carcinoma in situ subgroup, only cytokeratin 5/6 expression exhibited a negative association with the probability of invasion. CONCLUSION: The immunohistochemical expression of cytokeratin 5/6 by ductal carcinoma in situ epithelial cells may provide clinically useful information regarding the risk of progression to invasive disease.